Implementasi Manajemen Layanan Perpustakaan Umum pada Dinas Perpustakaan dan Arsip Kabupaten Tabanan - Putri Anggreni; Nur Mala Dewi (STIMI Handayani Denpasar, 2023)
This study aims to analyze the implementation of public library service management at the Tabanan Regency Library and Archives Service. This research is qualitative research. The results showed that the implementation of library service management at the Tabanan Regency Library and Archives Service had been implemented but was not optimal because there were still problems in its implementation. Planning (planning) at the Tabanan Regency Library and Archives Service has been carried out properly through the implementation of technical guidance for employees. Organizing, the availability of facilities and infrastructure resources at the Tabanan Regency Library and Archives Service still does not meet the needs of all levels of society in general. The actuating has been carried out but is not optimal due to inadequate human resources, limited funds owned by the Tabanan Regency Library and Archives Service in implementing the program, the lack of a collection of reading books owned by the Tabanan Regency Library and Archives Service. Supervision (controlling) shows that supervision has been carried out through regular meetings, tiered supervision, supervision of employee discipline but has not been optimal because the government's attention is still low on the development of public library functions.